Experimental investigation on the use of steel-concrete bond tests for estimating axial compressive strength of concrete. Part 2: APULOT - Silva, B. V. (2014)
The scope of this research investigates the feasibility to use steel-concrete bond tests for estimating the compressive strength of concrete to supplementary use it in the quality control of reinforced concrete. Lorrain and Barbosa (2008)[1] and Lorrain et al. (2011)[2] justify the use of a modified bond test, called APULOT, to estimate the compressive strength of concrete, thereby increasing the possibilities for the technological control of reinforced concrete at construction sites. They propose an adaptation of the traditional pull-out test (POT) method, standardized by CEB/FIP RC6:1983[3], as this is a low complexity test with the advantage of reduced costs. The use of the APULOT test as a technological control test of concrete at construction sites requires determining a standard and also adapting it from the experimental laboratory practice to the field. The first part of this work evaluated the potential to perform compressive strength estimates from the bond strength data obtained by the POT test. The second part of this paper will present and discuss the test results achieved by the APULOT method. Two concrete compositions of different classes (25 MPa and 45 MPa) were tested at 3, 7 and 28 days. Ribbed bar specimens (nominal diameters of 8, 10 and 12.5 mm) were also used in the preparation stage of the specimens, totaling 144 APULOT tests. The results show that under standard test conditions, the correlation between the maximum bond strength and the compressive strength of concrete is satisfactory at all ages tested, corroborating the objective of consolidating this test as a complementary alternative for controlling the quality of reinforced concrete.